Using Markets to Deal with Commodity Price Volatility : What Can Governments and Donors Do to Develop Markets that Ameliorate Commodity Price Volatility? - Larson, Donald; Varangis, Panos (World Bank, Washington, DC, 2012)
Commodities are often at the heart of local and sometimes national economies. Commodity prices are notoriously volatile, creating instability and uncertainty for commodity-dependent developing countries. Commodity price instability undermines economic growth and skews the distribution of income. As a result, nearly every government has tried to manage commodity price risks. This Note discusses different sets of commodity pricing policies and the barriers to their risk management.